2022
DOI: 10.3389/fmed.2022.967964
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and design of the prevention of paclitaxel-related neurological side effects with lithium trial – Protocol of a multicenter, randomized, double-blind, placebo- controlled proof-of-concept phase-2 clinical trial

Abstract: IntroductionChemotherapy-induced polyneuropathy (CIPN) and post-chemotherapy cognitive impairment (PCCI) are frequent side effects of paclitaxel treatment. CIPN/PCCI are potentially irreversible, reduce quality of life and often lead to treatment limitations, which affect patients’ outcome. We previously demonstrated that paclitaxel enhances an interaction of the Neuronal calcium sensor-1 protein (NCS-1) with the Inositol-1,4,5-trisphosphate receptor (InsP3R), which disrupts calcium homeostasis and triggers ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
(68 reference statements)
0
2
0
1
Order By: Relevance
“…The majority of studies have assessed paclitaxel-treated patients (cumulative n=349) and all have demonstrated increased NfL following treatment. [91][92][93][94][95] In 31 paclitaxel-treated patients with breast or ovarian cancer, elevations in NfL were correlated with clinically graded and patient-reported CIPN, with greater NfL associated with more severe CIPN. 91 NfL remained elevated at 28 weeks post-treatment but returned to baseline after 40 weeks.…”
Section: Emerging Biomarker Evidence Of Axonal Degenerationmentioning
confidence: 99%
“…The majority of studies have assessed paclitaxel-treated patients (cumulative n=349) and all have demonstrated increased NfL following treatment. [91][92][93][94][95] In 31 paclitaxel-treated patients with breast or ovarian cancer, elevations in NfL were correlated with clinically graded and patient-reported CIPN, with greater NfL associated with more severe CIPN. 91 NfL remained elevated at 28 weeks post-treatment but returned to baseline after 40 weeks.…”
Section: Emerging Biomarker Evidence Of Axonal Degenerationmentioning
confidence: 99%
“…A subsequent molecular analysis of cells exposed to antineoplastic agents at the threshold may identify biomarkers of CIPN or reveal pathways critical to preserving the neuron structure or function. With regard to the latter, preventative treatments that are currently undergoing trial or have demonstrated a reduced frequency and intensity of CIPN include oral cannabidiol, lithium, and zinc [ 142 , 143 , 144 ], which could be pre-administered as part of combinatorial therapy.…”
Section: Leveraging Gefb and Ipsc Technologies For Pre-clinical Appli...mentioning
confidence: 99%
“…Chemotherapien können kognitive Störungen ("cancer-related cognitive impairment") induzieren, die durch leichte bis mittelschwere kognitive Defizite gekennzeichnet sind, darunter Beeinträchtigungen der Verarbeitungsgeschwindigkeit, des Gedächtnisses, der exekutiven Funktionen und der Aufmerksamkeit. Bis zu 75 % der Patienten, die mit Chemotherapie gegen Krebserkrankungen außerhalb des Nervensystems behandelt werden, sind von kognitiven Defiziten betroffen [21,37]. Ein wichtiger Schritt in der Prävention der Alzheimer-Demenz wäre, diese Aspekte der kognitiven Sicherheit in der Versorgung zu berücksichtigen.…”
Section: Iatrogene Risiken Und Patientensicherheitunclassified